Identification of cis-acting determinants mediating the unconventional secretion of tau - Katsinelos, Taxiarchis; McEwan, William A.; Jahn, Thomas R.; Nickel, Walter (Scientific reports, 2021)
The deposition of tau aggregates throughout the brain is a pathological characteristic within a group of neurodegenerative diseases collectively termed tauopathies, which includes Alzheimer’s disease. While recent findings suggest the involvement of unconventional secretory pathways driving tau into the extracellular space and mediating the propagation of the disease-associated pathology, many of the mechanistic details governing this process remain elusive. In the current study, we provide an in-depth characterization of the unconventional secretory pathway of tau and identify novel molecular determinants that are required for this process. Here, using Drosophila models of tauopathy, we correlate the hyperphosphorylation and aggregation state of tau with the disease-related neurotoxicity. These newly established systems recapitulate all the previously identified hallmarks of tau secretion, including the contribution of tau hyperphosphorylation as well as the requirement for PI(4,5)P2 triggering the direct translocation of tau. Using a series of cellular assays, we demonstrate that both the sulfated proteoglycans on the cell surface and the correct orientation of the protein at the inner plasma membrane leaflet are critical determinants of this process. Finally, we identify two cysteine residues within the microtubule binding repeat domain as novel cis-elements that are important for both unconventional secretion and trans-cellular propagation of tau.